A Model Rural Inclusive Postsecondary Program for Students With Intellectual Disability. (December 2021) - Beckers, Gerlinde; Klein-Ezell, Colleen
Lions Connected (LC) is an inclusive postsecondary program approved by the U.S. Department of Education; thus meeting rigorous program standards and accountability. Equally important is that it gives eligible students from rural areas the opportunity to receive federal financial aid to attend college. The purpose of developing LC was to meet the needs and desires of the surrounding rural communities by providing postsecondary opportunities for students with intellectual disability (ID) to enhance their social, academic, and employment skills alongside peers without disabilities. This article describes the program in detail as well as program outcomes, including employment in rural home communities. LC students receive a true college experience while preparing to become contributing members in society regardless of where they live. By following LC's program structure, there are multiple opportunities for supporting students with ID in rural settings and helping them garner a college experience and become successfully employed in their community and reach their full potential.